1986
DOI: 10.1128/jb.167.3.1086-1088.1986
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of NAD metabolism in Salmonella typhimurium and cloning of the nadA and pnuC loci

Abstract: The nadA and pnuC loci of S. typhimurium were cloned and found to reside within a 2.2-kilobase region. Two-dimensional O'Farrell gel electrophoresis of the proteins produced after chloramphenicol amplificaton and subsequent release from chloramphenicol inhibition revealed NadA and PnuC to be 43,000-and 25,000-molecular-weight proteins, respectively. The data indicated that nadA and pnuC represent two distinct genes.The initial reactions in the biosynthesis of NAD in Salmonella typhimurium are catalyzed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This aspect of the model is indicated by the fact that nadRs superrepressor mutants grow poorly on NMN. This is not due to superrepression of the nadA pnuC operon causing lowered production of PnuC, since mutants carrying insertions and deletions in nadA remain PnuC+ due to the presence of an internal unregulated promoter for pnuC (27,29). The model also suggests that NadR interacts with PnuC at the membrane to function in the transport of NMN.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…This aspect of the model is indicated by the fact that nadRs superrepressor mutants grow poorly on NMN. This is not due to superrepression of the nadA pnuC operon causing lowered production of PnuC, since mutants carrying insertions and deletions in nadA remain PnuC+ due to the presence of an internal unregulated promoter for pnuC (27,29). The model also suggests that NadR interacts with PnuC at the membrane to function in the transport of NMN.…”
Section: Methodsmentioning
confidence: 84%
“…Both plasmids contained nadA and pnuC, but pTF15 contained an additional 2 kb of upstream sequence (27). Previous work with a chloramphenicol release method in conjunction with two-dimensional PAGE identified NadA and PnuC as 43-and 25-kDa proteins, respectively (27).…”
Section: Methodsmentioning
confidence: 99%
“…In cells lacking route 1, NMN assimilation was shown to depend on the PnuC transport protein and on a function of the NadR regulatory protein (37,41,48). A role for PnuC in transport is consistent with the multiple membrane-spanning domains of this molecule (34) and the presence of a functional signal sequence (48).…”
mentioning
confidence: 66%
“…Shortly after cloning of PnuC, it became evident that its activity strongly depends on the regulator NadR (Foster et al, 1987(Foster et al, , 1990Zhu et al, 1989. NadR was initially thought to have a regulatory as well as a transport function, because it is able to sense the internal NAD pool in order to repress essential genes for NAD biosynthesis [nadB, nadA-pnuC, and pncB (Spector et al, 1985;Cookson et al, 1987;Zhu et al, 1989;Penfound and Foster, 1999)] and to regulate transport via PnuC in response to cellular NAD levels (Tirgari et al, 1986;Foster et al, 1990;Foster and Penfound, 1993). Later, more specific enzymatic functions were assigned to NadR.…”
Section: A General Scheme For Pnu Transportermediated Uptakementioning
confidence: 99%
“…The name Pnu originates from the first member that was discovered over 30 years ago as a transport system involved in the uptake and utilization of pyridine nucleotides (Pnu -pyridine nucleotide uptake) (Kinney et al, 1979;Spector et al, 1985). The gene encoding PnuC from Salmonella typhimurium was cloned in 1986, and the protein was initially designated as the transporter of a previously characterized nicotinamide mononucleotide (NMN) uptake activity (Kinney et al, 1979;Liu et al, 1982;Spector et al, 1985;Tirgari et al, 1986;. Later studies showed that the substrate for PnuC is not NMN but its unphosphorylated precursor nicotinamide riboside (NR), which is one of the manifestations of vitamin B3, besides nicotinamide and nicotinic acid (Kemmer et al, 2001;Bieganowski and Brenner, 2004;Grose et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%